Degradation of p0071 and p120-catenin during adherens junction disassembly by Leptospira interrogans - Tokumon, Romina; Sebastián, Isabel; Humbel, Bruno M.; Okura, Nobuhiko; Yamanaka, Hidenori; Yamashiro, Tetsu; Toma, Claudia (Frontiers in Cellular and Infection Microbiology, 2023)
Leptospira interrogans disseminates hematogenously to reach the target organs by disrupting epithelial adherens junctions (AJs), thus causing leptospirosis, which is a globally neglected zoonotic disease. L. interrogans induces E-cadherin (E-cad) endocytosis and cytoskeletal rearrangement during AJ disassembly, but the detailed mechanism remains unknown. Elucidation of AJ disassembly mechanisms will guide new approaches to developing vaccines and diagnostic methods. In this study, we combine proteomic and imaging analysis with chemical inhibition studies to demonstrate that disrupting the AJs of renal proximal tubule epithelial cells involves the degradation of two armadillo repeat-containing proteins, p0071 and p120-catenin, that stabilize E-cad at the plasma membrane. Combining proteasomal and lysosomal inhibitors substantially prevented p120-catenin degradation, and monolayer integrity destruction without preventing p0071 proteolysis. In contrast, the pan-caspase inhibitor Z-VAD-FMK inhibited p0071 proteolysis and displacement of both armadillo repeat-containing proteins from the cell-cell junctions. Our results show that L. interrogans induces p120-catenin and p0071 degradation, which mutually regulates E-cad stability by co-opting multiple cellular degradation pathways. This strategy may allow L. interrogans to disassemble AJs and disseminate through the body efficiently.